2009
DOI: 10.1016/j.jas.2009.06.022
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the site specificity of soil elemental signatures for identifying and interpreting former functional areas

Abstract: Soil multi-element analysis is now a routine technique employed to help answer questions about space use and function in and around archaeological sites. The pattern of enhancement of certain elements, including P, Pb, Ca, Zn, and Cu, has been shown by numerous studies to correlate closely with the archaeological and historical record.Interpretation of these soil signatures, however, has generally been more problematic.One approach to the problem has been the use of ethnographic or "known" sites to guide inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 37 publications
(42 reference statements)
1
35
0
2
Order By: Relevance
“…Quantitative analysis of archaeological sediments was carried out to measure nine inorganic elements commonly reported as being associated with anthropogenic activity and arable augmentation (Aston et al, 1998;Holliday and Gartner, 2007;Wilson et al, 2008Wilson et al, , 2009Alexander et al, 2012). Aeolian deposit and slow-moving entrained alluvial surface deposition; dark grey (7.5YR 6/2); clay silts and unsorted angular fine gravels (10%); c/f 1:9; roots were visible (20%); weakly developed subangular peds and a diffused boundary above (4049); distinct boundary below (4041) 4041 45-90 6.9 Aeolian deposit and slow-moving entrained alluvial sediment; silty clay (7.5YR 5/2) sand; unsorted angular gravel (vf, 5%; f, 10%); c/f 1:4; visible fine root; faunal burrows (20%); weakly angular peds; distinct boundary 4041-4048 4042 90-120 7.0 Alluvial overbanking deposits of the phase 2 channel; grey brown (10YR 5/2); silty clay; subangular sand/gravel coarse fraction (f, S); c/f 3:7; visible roots/rootlets; moderately developed platy peds; well-defined boundary 4043 120-130 7.1 Moderate-/fast-flowing fine alluvial irrigation deposits (phase 2); greyish brown (7.5YR 4/1); silty clay; root (5%); mesofaunal burrows; partially sorted angular/subangular gravels (vf, 10%; f, 10%; S, 20%); c/f 2:3; subangular peds; channel and chamber voids 4046 150-160 6.9 Slow-flowing alluvial irrigation deposit (phase 2); brown yellow (10YR 4/6); clay silt; c/f 1:4; with subangular sand and gravel (vf, 10%; f, 5%; S, 5%; M, 5%); moderately developed subangular blocky peds; distinctive boundaries 4044 125-145 6.9 Slow-flowing alluvial irrigation deposits (phase 1 channel); brown grey (7.5YR 6/2); silty clay sands; roots (2%); c/f 1:9; sorted subangular gravels (vf, 5%; f, 10%; S, 10%; M, 5%); moderately developed platy peds; distinct boundaries 4045 145-160 7.0 Slow-flowing alluvial irrigation deposits (phase 1 channel); brown grey (7.5YR 4/1); clay silt; c/f 1:1; roots visible (2%); unsorted angular gravels (vf, 10%; f, 5%; S, 5%; M, 5%); subangular peds (compacted); well-defined boundaries These are: aluminium (Al), phosphorus (P), potassium (K), calcium (Ca), chromium (Cr), manganese (Mn), iron (Fe), zinc (Zn), and strontium (Sr).…”
Section: Geochemical Analysismentioning
confidence: 99%
“…Quantitative analysis of archaeological sediments was carried out to measure nine inorganic elements commonly reported as being associated with anthropogenic activity and arable augmentation (Aston et al, 1998;Holliday and Gartner, 2007;Wilson et al, 2008Wilson et al, , 2009Alexander et al, 2012). Aeolian deposit and slow-moving entrained alluvial surface deposition; dark grey (7.5YR 6/2); clay silts and unsorted angular fine gravels (10%); c/f 1:9; roots were visible (20%); weakly developed subangular peds and a diffused boundary above (4049); distinct boundary below (4041) 4041 45-90 6.9 Aeolian deposit and slow-moving entrained alluvial sediment; silty clay (7.5YR 5/2) sand; unsorted angular gravel (vf, 5%; f, 10%); c/f 1:4; visible fine root; faunal burrows (20%); weakly angular peds; distinct boundary 4041-4048 4042 90-120 7.0 Alluvial overbanking deposits of the phase 2 channel; grey brown (10YR 5/2); silty clay; subangular sand/gravel coarse fraction (f, S); c/f 3:7; visible roots/rootlets; moderately developed platy peds; well-defined boundary 4043 120-130 7.1 Moderate-/fast-flowing fine alluvial irrigation deposits (phase 2); greyish brown (7.5YR 4/1); silty clay; root (5%); mesofaunal burrows; partially sorted angular/subangular gravels (vf, 10%; f, 10%; S, 20%); c/f 2:3; subangular peds; channel and chamber voids 4046 150-160 6.9 Slow-flowing alluvial irrigation deposit (phase 2); brown yellow (10YR 4/6); clay silt; c/f 1:4; with subangular sand and gravel (vf, 10%; f, 5%; S, 5%; M, 5%); moderately developed subangular blocky peds; distinctive boundaries 4044 125-145 6.9 Slow-flowing alluvial irrigation deposits (phase 1 channel); brown grey (7.5YR 6/2); silty clay sands; roots (2%); c/f 1:9; sorted subangular gravels (vf, 5%; f, 10%; S, 10%; M, 5%); moderately developed platy peds; distinct boundaries 4045 145-160 7.0 Slow-flowing alluvial irrigation deposits (phase 1 channel); brown grey (7.5YR 4/1); clay silt; c/f 1:1; roots visible (2%); unsorted angular gravels (vf, 10%; f, 5%; S, 5%; M, 5%); subangular peds (compacted); well-defined boundaries These are: aluminium (Al), phosphorus (P), potassium (K), calcium (Ca), chromium (Cr), manganese (Mn), iron (Fe), zinc (Zn), and strontium (Sr).…”
Section: Geochemical Analysismentioning
confidence: 99%
“…There are many studies focusing on multi-element analyses bringing similar results (Bindler et al 2011;Bing et al 2011;Costa 2011;Davidson et al 2007;Entwistle et al 1998Entwistle et al , 2000Facchinelli et al 2001;Horák, Hejcman 2016a;2016b;Sollito et al 2010;Walkington 2010;Wilson et al 2009). It was also shown that it is highly suitable to work more with the multivariate analyses results rather than with the original concentrations, or the transformed concentrations, i.e.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Facchinelli et al 2001) than in the archaeological literature, where the analysis of separate elements prevails (e.g. Bindler et al 2011;Wilson et al 2005), although in some cases multivariate analyses are being used to find the connections (Entwistle et al 1998;Wilson et al 2008Wilson et al , 2009). There should also be more research of soils in the areas of abandoned villages, not only in general gradients or in regular grids, but also with respect to different possessions.…”
Section: In Som)mentioning
confidence: 99%
See 1 more Smart Citation
“…Hipótesis antropogénica: Los horizontes húmicos ah no estarían formados cuando se establecen las primeras sociedades neolíticas. Estas sociedades producirían una cantidad elevada de materia orgánica proveniente, en primer lugar, del aporte de los carbones al quemar la vegetación, pero también de todo tipo de desechos asociados a las actividades realizadas en el entorno de las viviendas, así como durante el proceso de amortización de éstas (Stevanovic 1997;Wilson et al 2009). Procesos similares de formación de los suelos se han documentado tanto en la selva amazónica, en los llamados Terra Preta Soils 12 (Lehmann et al 1993) como en zonas del mediterráneo europeo (Nicosia et al e.p.).…”
Section: Spal 18 (2009): 41-52unclassified